2008
DOI: 10.1093/ndt/gfn304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amlodipine on cardiovascular events in hypertensive haemodialysis patients

Abstract: Background. Hypertensive haemodialysis patients may be at a high risk for cardiovascular events. This study was undertaken to ascertain whether the calcium channel blocker amlodipine reduces mortality and cardiovascular events in these high-risk patients.Methods. We evaluated the effects of amlodipine on cardiovascular events in 251 hypertensive haemodialysis patients in an investigator-designed, prospective, randomized, double-blind, placebo-controlled, multicenter trial. One hundred and twenty-three patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 20 publications
3
76
0
2
Order By: Relevance
“…This patient was on lisinopril and metoprolol. Amlodipine is a reasonable third-line agent given its long half-life, and at least in one randomized prospective clinical trial in ESRD patients, it did not increase the incidence of IDH (16). We avoid short-acting drugs, such as clonidine, that need to be administered frequently whenever possible.…”
Section: Treatmentmentioning
confidence: 99%
“…This patient was on lisinopril and metoprolol. Amlodipine is a reasonable third-line agent given its long half-life, and at least in one randomized prospective clinical trial in ESRD patients, it did not increase the incidence of IDH (16). We avoid short-acting drugs, such as clonidine, that need to be administered frequently whenever possible.…”
Section: Treatmentmentioning
confidence: 99%
“…Уменьшение протеинурии на фоне приема ам-лодипина было доказано не во всех исследованиях, но как показали результаты исследования Tepel M и совт., у больных хроническими заболеваниями почек, находящимися на гемодиализе, назначение амлодипина сопровождается значительным сниже-нием риска развития нежелательных сердечно-со-судистых событий [60].…”
Section: антагонисты кальцияunclassified
“…The cardioselective β-blockers (β₁-blockers) such as metoprolol and atenolol have been studied in patients with essential hypertension with normal renal function, hypertension along with diabetic nephropathy and ESRD with dialysis and demonstrated that neither metoprolol nor atenolol produce significant reduction in GFR or renal blood flow while effectively lowering blood pressure in patients with essential hypertension, although both can increase renovascular resistance [32,33]. Studies with metoprolol and atenolol in patients with ESRD on chronic dialysis or after kidney transplantation have demonstrated no adverse effects on renal hemodynamics [34,35].…”
Section: Beta Blockers In Haemodialysis Patientsmentioning
confidence: 99%